دراسة تحليلية للعمران الصحراوي في البادية السورية نحو منهج لتحديد كودات وتشريعات تخطيطية أكثر تلاؤما باستخدام برنامج s.p.s.s/win - صيداوي وليد عدنان (Latakia University Journal -Engineering Sciences Series, 2019)
إن فقدان الكودات التخطيطية والتصميمية في البيئات المختلفة وخاصة الصحراوية منها (لشدة تأثرها بالمتغيرات المؤثرة ، بيئة ،اقتصادية، اجتماعية...الخ) تجعل العمران في هذه المناطق الصحراوية خاضعاً لتنمية عمرانية فوضوية بعيدة عن منظومة البناء والملاءمة والاستمرار بالشكل الأفضل. وعليه هدف الباحث إلى : 1- تحديد المتغيرات المؤثرة في العمران الصحراوي ؛ 2- بيان مدى ملاءمة الكودات التخطيطية والتصميمية لاحتياجات السكان عبر سبر هذه الاحتياجات وقياس توافقها مع الكودات باستقصاء ميداني إحصائي ومن وجهات نظر عدة (اجتماعية ، اقتصادية ، مهتمين.... ..) ؛ 3- تحديد الأسباب وراء قيم درجة الملاءمة بدراسة تحليلية تهدف إلى استبعاد السلبيات وإبراز الإيجابيات بهدف رفع درجة الملاءمة في إطار المنفعة العامة؛ 4- صياغة منهج يتيح تحديد كودات ديناميكية متطورة عبر تحليل قاعدة بيانات قوامها قياس المتغيرات المؤثرة في واقع مكاني صحراوي محدد. يقوم البحث على أربعة أجزاء وهي : 1- الدراسة النظرية: تبحث في الواقع العمراني الصحراوي وبيان أسباب غياب المعايير الملائمة فيه. ومن أهم هذه الأسباب عدم الأخذ بالمؤثرات والمتغيرات الفاعلة بالعمران الصحراوي بشكل دقيق وعلمي في صياغة الشكل النهائي للكودات والمعايير. وتخلص الدراسة النظرية لاستنتاج المتغيرات المؤثرة وطرق قياسها في العمران الصحراوي. 2- الدراسة الميدانية :إنشاء قاعدة بيانات وذلك بقياس المتغيرات المحددة سابقاً في واقع مكاني صحراوي من البادية السورية وذلك من خلال مسح ميداني. 3- الدراسة التحليلية: تحليل قاعدة البيانات السابقة عبر برنامج إحصائي s.p.s.s/win لاستنتاج التالي: - بيان العلاقات الترابطية cor. Coff بين المتغيرات المؤثرة في ذاك العمران وبيان أهمها ومدى شدتها واتجاهاتها؛ - إيجاد معادلات ونماذج رياضية – إحصائية (عناصرها المتغيرات المؤثرة )؛ - تحدد كودات ديناميكية للتجمعات العمرانية الصحراوية تجعل الإنسان ومحيطه الحيوي أكثر تلاؤماً وانسجاماً وتطوراً وذلك بعد قياس المتغيرات المؤثرة وشدتها واتجاهها في هذا العمران وتطبيقها في النماذج المستخرجة سابقا. 4- الاستنتاجات: الخروج بمنهج لتحديد معايير ديناميكية وليست استاتيكية تضمن لهذه التجمعات التي توجد في بيئات شديدة الحساسية أن تبقى وتستمر وتتلاءم وتتطور في إطار محيطها الحيوي. Introduction: The lack of planning and designing codes in various environments, especially the desert environment, (being highly influenced by the effective variables environmental, economical, social, etc) makes urbanization in these desert areas subject to chaotic urban development far from the system of urbanization, convenience and durability in the best possible way. Accordingly, this research attempts to : 1- Define the variables which affect desert urbanization. 2- Define the extent of convenience of planning and designing codes to the needs of the people by studying these needs and measuring their coordination with the codes, through field statistic research, and from different views (social, economical, concerned, etc..) 3- Define the reasons behind the values of the elements degree of convenience, through an analytical study aiming at rejecting the negative, and enlarging the positive ones, in order to elevate the degree of convenience in the frame of common benefit. 4- Formulate a method which makes it possible to define dynamic and developed codes through Data base analysis depending on measuring the variables which affect the facts of a definite desert location. The structure aims to: 1- Theoretical study: Discusses the facts of desert urbanization and clarifies the reasons of the lack of proper scales in it. One of the most important of these reasons is the inaccurate and unscientific consideration of these influences and variables effective in desert urbanization in the formation of the final shape of codes and scales. The theoretical study aims at deducing the effective variables and ways of measuring them in desert urbanization. 2- Field study: will be accomplished in two ways, the first way is investigating the phenomena of convenience of a real desert location. The second is forming a data base by measuring the variables effective previously defined in one desert location in Syrian Baiyah by means of a field survey. 3- Analytical study: will be accomplished in two ways. The first is detecting the reasons of the values of convenience and how to elevate them. The second is analyzing the previous data base by statistic program s.p.s.s/win (statistical program social science) to conclude the following :To clarify the cor.Coff among the effective variables in that urbanization, its importance, and the extent of its tension and direction.Finding formulae and mathematical-statistical types (their elements are the effective variables) which define dynamic codes of the desert urbanized gatherings which make man and his vital surrounding more convenient, more harmonized and more developed, after measuring the effectives variables, their intensity and direction in this urbanization, and implementing them in the previously concluded types. 4- Conclusions: To form dynamic scales that are not static, and that ensure that these gatherings, which are founded in very sensitive environments, can remain, continue, fit and develop within their vital surrounding.